Reduction of Intestinal Motility and Contractility in The Cats Anethetized with Tiletamine-Zolazepam Through Contrast Radiography Study - Deni Noviana; Ajeng Kandynesia (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Intestinal motility and contractility in cats can be affected by many factors that originate from inside and outside the body. Anesthesia is one of the factors that could influence it.This research was conducted to figure the effect of tiletamine-zolazepam on the intestinal motility and contractility in the cats through contrast radiography study. Three male cats weighing between 2,5-3,5kg were used in this present study. Radiography procedure was performed twice on each cat: without anesthesia and one week later with anesthesia (0,02 mg/BW atropine sulphate and 10 mg/BW Zoletil®).The cats were given a positive contrast, barium sulphate (BaSO4) 30% w/v (12 ml/kg BWper oral) followed by radiography study. Radiography was performed at 5, 30, 60, 120, and 180 minutes after administration of BaSO4. The cats were positioned on laterolateral view. Data were analyzed descriptively using zone division and quantitatively by measuring the difference between the intestines diameter during contraction and relaxation. The intestinal diameter was measured and statistically tested using ANOVA. Result showed that in minute 180, BaSO4 reached zone four in the unanesthetized cat while in the anesthetized cat, it was still empty. The diameter differences of the unanesthetized cat was higher compared to the anesthetized meaning that the intestinal contraction in the unanesthetized cat was higher. This means that tiletamine-zolazepam anesthetic reducedof intestinal motility andcontractility. Keywords: cats, barium sulphate, gastrointestinal motility, contrast radiography, tiletamine-zolazepam